Manfaat Sistem Informasi Dalam Manajemen Pemasaran Produk Melalui Tiktok - Hayfa Azwa Fadila; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2023)
Product marketing is an important aspect in promoting products so that they are known among many people. Tiktok is not only used as an entertainment medium, but tiktok can be used as a stall to promote products and save the on rental costs. Tiktok is a social media platform for sharing video content that is 15 seconds long or can be combined into 60 seconds. This video can be an effective promotional medium.